SHARIA COMPLIANCE DALAM PEMBIAYAAN KEPEMILIKAN RUMAH DI PERUMAHAN SML GARDEN : Studi Kasus di Perumahan SML Garden, Jln. Tanjung Harapan, Tembilahan Kota, Kabupaten Indragiri Hilir - Junaidi Junaidi; M Aldi; Najamuddin Najamuddin (LPPM Universitas Islam Indragiri, 2025)
This study aims to analyze the level of Sharia compliance in home ownership financing at SML Garden Housing, Tembilahan. The phenomenon of the widespread use of the label “Sharia” in the property sector raises questions about the substantive compatibility of the contracts used, and to what extent Sharia principles—such as justice, transparency, and freedom from riba (usury)—are actually implemented. Utilizing a qualitative descriptive approach through a case study method, involving in-depth interviews with homeowners, employees, and consumers of the housing development, the results indicate that SML Garden Housing has generally implemented Sharia principles, particularly by avoiding riba and providing flexible payment options. However, challenges remain in terms of formal documentation, cost transparency, and the existence of an independent Sharia supervisory body. This research contributes to strengthening the practice of Sharia-based property financing at the community and developer levels.